Neurohormonalna regulacja dynamiki cieczy wodnistej jako podstawa farmakoterapii jaskry. Część I – Produkcja cieczy wodnistej - Terelak-Borys, Barbara; Liberek, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
The aim of this article is to present current opinion on aqueous humor dynamics regulation and antiglaucoma drugs mechanisms of action. Glaucoma pharmacotherapy is based mainly on neuro-hormonal processes controlling aqueous humor dynamics. Systemic hormones as well as local hormones and autonomic nervous system mediators are involved in the processes of aqueous humor formation and drainage. Antiglaucoma medications act mainly through activation or inhibition of these systems’ receptors, helping to decrease aqueous humor production or improve aqueous humor outflow. In this article (part 1) we describe three groups of antiglaucoma medications (beta-antagonists, adrenergic agonists, carbonic anhydrase inhibitors), inhibiting the aqueous humor production and mechanisms of their hypotensive effect in the eye.